Perbandingan peningkatan Pembelajaran Berbasis Proyek Dan Pembelajaran Kontekstual Terhadap Peningkatan HOTS Siswa Pada Materi Sejarah Indonesia - Adriyansyah; Trimurtini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to compare the effectiveness of project-based learning (PBL) and contextual learning methods in improving Higher Order Thinking Skills (HOTS) of grade XI students in the subject of Indonesian History. The subjects of the study consisted of two classes: grade XI.10 taught using the PBL method, and grade XI.4 taught using the contextual method. The research design used was a quasi-experimental design with a pre-test-post-test control group design. Data were obtained through HOTS tests before and after treatment, then the scores of each class were calculated. The results of the analysis showed that the average gain score of grade XI.4 students (contextual method) was 11.2, higher than grade XI.10 (PBL method) of 7.1. Normality and homogeneity tests showed that the data were normally distributed and homogeneous. Hypothesis testing using the Independent Sample t-test produced a significance value of 0.017 (<0.05) which indicated a significant difference between the two groups. Thus, it can be concluded that the contextual learning method is more effective than the PBL method in improving students' HOTS in the subject of Indonesian History. The results of this study support the application of a contextual approach to improve student abilities.